Salvage surgery with second free flap reconstruction for recurrent oral squamous cell carcinoma. Issue 6 (June 2020) - Jung, Tae-Young; Sung, Ki-Woong; Park, Sang-Yoon; Kim, Soung-Min; Lee, Jong-Ho
Abstract: Purpose: The purpose of this study was to evaluate the results of the reconstruction using the second free flap following resection of recurrent oral squamous cell carcinoma(OSCC). Patients and methods: A total of 25 patients from 2005 to 2018 who had undergone salvage surgery and reconstruction using the second free flap for recurrent OSCC were included in this study. Medical records were reviewed to obtain demographic data, stages of the primary cancer, region of recurrent OSCC, the period until recurrence, type of the second reconstruction flaps, recipient vessels, survival rate of the flaps and 2- and 5-year survival rates. Results: The patients were 13 males and 12 females. The average age was 64.1 years. Of the stages of primary cancer, stage IV patients accounted for the largest number with 13 patients (52.0%). The region of recurrent OSCC was the largest in the mandible with 13 patients, followed by 5 patients in the tongue and 4 patients in the buccal mucosa and maxilla. The mean time interval between the first and second reconstruction was about 34.1 months. Latissimus dorsi free flap and radial forearm free flap used in the second reconstruction were most frequently used in 11 patients (35.5%), followed by fibular composite free flap with 6 patients (19.4%). Facial artery in the recipient arteries of the second reconstruction was most frequently used with 13 cases (43.3%), followed by superior thyroid artery with 8 cases (26.7%) and lingual artery with 7 cases (23.3%). In the second free flap reconstruction, survival rate of the flaps was 96.8%. The 2- and 5-year survival rates in the patients were 70.0% and 62.5%, respectively. Conclusion: The study showed that the second free flap reconstruction with salvage surgery in resectable recurrent OSCC is a safe and reliable method with a high success rate of the flap and improvement of the 5-year survival rate. Abstract : Pathology; Cancer Surgery; Dental Surgery; Rehabilitation; Oncology; Recurrent oral squamous cell carcinoma, Second free flap reconstruction.